Correction: Multi-methodological approach for the Quality assessment of Senecionis scandentis Herba (Qianliguang) in the herbal market. - Hiu-Lam Ngai; Xiao Yang; Adrian Jun Chu; Rachel Harper; Alice B J E Jacobsen; David Tai-Wai Lau; Ho-Yin Yu; Hung-Kay Lee; Pang-Chui Shaw (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0267143.].